2022
DOI: 10.1002/sim.9552
|View full text |Cite
|
Sign up to set email alerts
|

Single‐stage, three‐arm, adaptive test strategies for non‐inferiority trials with an unstable reference

Abstract: For indications where only unstable reference treatments are available and use of placebo is ethically justified, three-arm "gold standard" designs with an experimental, reference and placebo arm are recommended for non-inferiority trials.In such designs, the demonstration of efficacy of the reference or experimental treatment is a requirement. They have the disadvantage that only little can be concluded from the trial if the reference fails to be efficacious. To overcome this, we investigate novel single-stag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(46 citation statements)
references
References 21 publications
0
44
2
Order By: Relevance
“…The maximum observed loss in probability of success observed in our simulations was about 1%, which is quite low considering the benefit in interpretation the SCIs offer. Throughout all simulations, we observed that the single-step confidence intervals interpreted with the help of the superiority filter yielded a lower probability of success than the procedure of Brannath et al 3 or the informative SCIs. The loss in probability of success compared to using the informative SCIs amounted up to ∼ 10% in some scenarios.…”
Section: Probability Of Successmentioning
confidence: 76%
See 3 more Smart Citations
“…The maximum observed loss in probability of success observed in our simulations was about 1%, which is quite low considering the benefit in interpretation the SCIs offer. Throughout all simulations, we observed that the single-step confidence intervals interpreted with the help of the superiority filter yielded a lower probability of success than the procedure of Brannath et al 3 or the informative SCIs. The loss in probability of success compared to using the informative SCIs amounted up to ∼ 10% in some scenarios.…”
Section: Probability Of Successmentioning
confidence: 76%
“…The method presented by Brannath et al 3 can also be applied to our setup with the IU filter (3). We want to compare the optimal sample sizes derived for this setup to those derived for the superiority filter (4).…”
Section: Optimal Sample Sizesmentioning
confidence: 99%
See 2 more Smart Citations
“…While Homma and Daimon already present operating characteristics for optimally chosen allocation ratios for their rerandomization procedure, one could try to find optimal design parameters for this design with added futility boundaries or an additional group sequential recruitment stage. Another interesting modification of the gold‐standard design, introduced by Brannath et al 31 is the idea of adaptively switching from testing non‐inferiority of treatment against control to testing delta‐superiority of treatment over placebo in cases where the control treatment turns out to be non‐effective. Especially in group sequential recruiting procedures, this modification might also benefit from optimal design parameter choices.…”
Section: Discussionmentioning
confidence: 99%